2012
DOI: 10.1371/journal.pone.0048354
|View full text |Cite
|
Sign up to set email alerts
|

Association between Extremely Low-Frequency Electromagnetic Fields Occupations and Amyotrophic Lateral Sclerosis: A Meta-Analysis

Abstract: ObjectivesTo estimate the relationship between exposure to extremely low-frequency electromagnetic fields (ELF-EMF) and the risk of amyotrophic lateral sclerosis (ALS) by a meta-analysis.MethodsThrough searching PubMed databases (or manual searching) up to April 2012 using the following keywords: “occupational exposure”, “electromagnetic fields” and “amyotrophic lateral sclerosis” or “motor neuron disease”, seventeen studies were identified as eligible for this meta-analysis. The associations between ELF-EMF e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
(118 reference statements)
2
53
0
2
Order By: Relevance
“…Exposure to electromagnetic fields has been studied in epidemiological [62][63][64][65][66], observational [67] and laboratory works [68]. A recent meta-analysis suggests a slightly but significantly increased risk of ALS among workers exposed to an extremely low frequency electromagnetic field (ELF-EMF), but does not deny the possibility of bias in the data analysis [69]. However, in the case of electromagnetic fields, there are many problems: at present, no apparent correlation between the exposure assessment and the observed associations is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to electromagnetic fields has been studied in epidemiological [62][63][64][65][66], observational [67] and laboratory works [68]. A recent meta-analysis suggests a slightly but significantly increased risk of ALS among workers exposed to an extremely low frequency electromagnetic field (ELF-EMF), but does not deny the possibility of bias in the data analysis [69]. However, in the case of electromagnetic fields, there are many problems: at present, no apparent correlation between the exposure assessment and the observed associations is possible.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, two meta-analysis studies have analysed the previously reported associations of occupational magnetic field exposure with amyotrophic lateral sclerosis. Zhou et al (2012) reported significant increases in risk of ALS due to ELF-MF exposure based on 9 case-control studies (RR = 1.39) but not in 8 cohort studies (RR = 1.16, CI: 0.80-1.69). Similar findings are illustrated in the meta-analysis from Vergara et al (2013), who analysed 12 case-control studies reporting a significant increased risk of 1.38 for ALS, but again a weak associated risk of 1.14 from 9 cohort studies.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 91%
“…ELF-EMFs have frequencies ranging from 3 Hz to 3,000 Hz. Electricians, electrical and electronic equipment repairers, train drivers, telephone installers or repairers and machinists are constantly exposed to them (Zhou et al, 2012). Håkansson et al (2003) assessed the impact of ELFEMFs in a cohort of Swedish engineering industry workers and highlighted an increased risk of Alzheimer's disease (relative risk, RR 0.4; 95% CI 1.4-11.7) and of ALS (RR 2.2; 95% CI 1.0-4.7).…”
Section: Electromagnetic Fields and Electric Shocksmentioning
confidence: 99%
“…Similar results were reported by Huss et al (2014), comparing ALS mortality in 2000-2008 and job exposure to ELF-EMFs and electric shocks in the Swiss National Cohort. In 2012 an interesting meta-analysis of seventeen studies (Zhou et al, 2012) found an increased risk of ALS in pooled studies (RR 1.29, 95% CI 1.02-1.62), and in case-control studies, with an odds ratio (OR) of 1.39 (95% CI 1.05-1.84), but not in cohort studies, in which the RR was 1.16 (95% CI 0.80-1.69). The authors affirmed that the RR value was not high enough to exclude the possibility of biases.…”
Section: Electromagnetic Fields and Electric Shocksmentioning
confidence: 99%